Effectiveness of coordination training in technical preparation of freestyle wrestlers at various levels of sports advancement - Gierczuk, D.; Sadowski, J. (Archives of Budo, 2010)
Study aim: The aim of the study was to evaluate the effectiveness of special coordination training in technical preparation of freestyle wrestlers at various levels of sports advancement. Material/methods: Freestyle wrestlers aged 14-15 and 18-19 participated in the research. The main research tool was a pedagogical experiment which consisted in implementing a set of special coordination exercises in a training process. Results: An increase in the volume of coordination means in training helped to improve considerably the quality of performing selected technical elements. The most significant increase was observed in those technical elements which, according to experts` evaluation, were the least mastered prior to the experiment. Wrestlers with shorter training experience manifested a larger transfer of coordination training effects on technical skills than those with longer training experience. Conclusions: Special coordination training may constitute an integral part of the training process and may be used as one of the means whereby the effectiveness of training in wrestling at all levels of sports advancement is enhanced. While planning coordination training it is necessary to define its independent goals and tasks simultaneously taking into consideration the primary role of the general objective of training.